MANAJEMEN STRATEGI PESANTREN DALAM MELESTARIKAN NILAI KEISLAMAN DI TENGAH ARUS GLOBALISASI TEKNOLOGI CERDAS - nazilatun nuroini; Imam Khaudli (BAMALA Institute, 2025)
Islamic boarding schools, as Islamic educational institutions, face new demands in the era of smart technology globalization, which demands strengthened strategic management to maintain Islamic values ​​while meeting the needs of global competency. Survey results in Java and various Islamic boarding schools in Indonesia indicate that digital transformation has generated diverse opinions from educators. Some embrace technology as a means of strengthening learning effectiveness and increasing student competitiveness, while others reject it due to concerns that technology will erode the spiritual depth, discipline, and scientific traditions of Islamic boarding schools. Furthermore, the community, as a key stakeholder, has also shown resistance, particularly regarding the use of devices, the potential for internet misuse, and concerns about reducing student simplicity. In some areas, there have even been open protests against the digitalization of Islamic boarding schools. Other findings indicate significant differences in student academic outcomes, with Islamic boarding schools that integrate technology moderately to intensively experiencing improvements in academic achievement, digital literacy, and adaptability, while those with minimal technology tend to stagnate and are less prepared for digital-based exams or competitions. The diverse perceptions of educators, community resistance, and variations in academic achievement demonstrate the need for a systematic and balanced Islamic boarding school management strategy, ensuring that technological integration does not diminish Islamic character but instead strengthens the effectiveness of learning and the relevance of Islamic boarding school education amidst the demands of the global era. Therefore, Islamic boarding schools are required to formulate a strategic approach that integrates tradition, spiritual values, and technological innovation to produce a generation with strong and competitive character.